EDUCATIONAL VALUES ON ENGLISH ISLAMIC SONG LYRICS OF SAMI YUSUF ALBUM - Septiyana, Linda; Kuryani, Kuryani; gestiana, silvia (ETERNAL (English, Teaching, Learning, and Research Journal), 2021)
Educational values can influence people’s behaviour and daily life. Besides, educational values can create good characters of human beings. This study aims : 1) to find out educational values in English Islamic song lyrics of Sami Yusuf album and 2) to analyze educational values in English Islamic song lyrics of Sami Yusuf album. This research is a content analysis study that includes descriptive analysis. The data collecting techniques used by researchers were observation and documentation. The result shows the educational values that are found in Sami Yusuf’s song lyrics deal with honesty, courage, peace, self-reliance & potential, self-discipline & moderation, loyalty & dependability, respect, love, sensitive & unselfishness, kindness & friendliness, and justice & mercy. The highest educational value that is found is honesty which is 19%, while the least are peace, respect, and love that are only found once with a percentage of 3% each of them. Therefore, it is recommended for English teacher to use English Islamic song lyrics in Sami Yusuf album as a medium in teaching and learning. Teachers do not have to worry because the songs in this album contain a variety of positive values that can be used in the learning process.